THE DROUGHT OF 2022 IN THE WESTERN PLAIN LOCATED NORTH OF THE MUREȘ RIVER – ROMANIA - Şerban Eugenia; Crainic Ghiță Cristian; Tătar Corina; Linc Ribana; Curilă Mircea; Sabău Nicu Cornel (Natural Resources and Sustainable Development)
The paper analyzed the annual and monthly number, duration and frequency of drought and dryness periods, from the year 2022. The periods of drought and those of dryness were established according to the definitions given by Hellman. They were extracted from daily precipitation data from five weather stations located in the Western Plain north of the Mureș River. Since the periods of drought and dryness have different durations, the number of days of drought and dryness was analyzed, providing a more accurate analysis of the phenomena. The annual and monthly precipitation amounts of the year 2022, as well as the monthly maximum air temperatures, were also analyzed. The result was that between 5 and 8 periods of drought were recorded on the studied territory, with an average duration of 14-15 days and between 8 and 17 periods of dryness, with an average duration of 6-7 days. That is, the drought and dryness lasted about 5-6 months (and almost 7 months in the south of the plain). Drought was more intense on the territory north of Mureș, while dryness prevailed south of Mureș, in 2022 (opposite than usual). The number of drought days was double or almost double the average of the period 1961-2000, on most of the territory north of Mureș. The drought was unusually long in the north of the plain. The year 2022 had a very intense early spring drought, an intense autumn drought, and an intense summer drought. The summer drought overlapped with repeated heatwaves, with extreme temperatures, which affected the regional economy.